2009
DOI: 10.1002/stem.109
|View full text |Cite
|
Sign up to set email alerts
|

mAb 84, a Cytotoxic Antibody that Kills Undifferentiated Human Embryonic Stem Cells via Oncosis

Abstract: The monoclonal antibody mAb 84, which binds to podocalyxin-like protein-1 (PODXL) on human embryonic stem cells (hESCs), was previously reported to bind and kill undifferentiated cells in in vitro and in vivo assays. In this study, we investigate the mechanism responsible for mAb 84-induced hESCs cytotoxicity. Apoptosis was likely not the cause of mAb 84-mediated cell death because no elevation of caspase activities or increased DNA fragmentation was observed in hESCs following incubation with mAb 84. Instead,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 61 publications
2
91
1
Order By: Relevance
“…Notably, podocalyxin binds to actin through ezrin, 72 and the antigen recognized by 84 mAb is a podocalyxin-like protein. 51 In the case of cells treated with 84 mAb 52 and KID3/RAV12, 48 a disruption of the actin cytoskeleton was observed.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, podocalyxin binds to actin through ezrin, 72 and the antigen recognized by 84 mAb is a podocalyxin-like protein. 51 In the case of cells treated with 84 mAb 52 and KID3/RAV12, 48 a disruption of the actin cytoskeleton was observed.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 98%
“…51 The 84 mAb induced membrane pores in treated cells. 52 Another well characterized antibody exhibiting this effect on plasma membrane is 14F7 mAb, 53 which targets the tumor-associated GM3(Neu5Gc). 14 14F7 mAb.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…The selective elimination of undifferentiated PSC populations could be performed via specific induction of apoptosis (e.g. mab 84 or ceramides) or cell depletion with magnetic-activated cell sorting (Bieberich et al 2003;Tan et al 2009;Diogo et al 2012). The detection of histocompatibility complexes enables the creation of stem cell banks to preserve patient-specific cell lines (e.g.…”
Section: Automation Devices For Stem Cell Productionmentioning
confidence: 99%
“…The mechanism for mAb 84 cytotoxicity is not dependent on complement activation, hypercrosslinking of bound antibody or antibody internalization. Instead, mAb 84 mediates cell death by oncosis initiated by PC-mediated reassembly of cytoskeleton, degradation of cytoskeletal structural proteins (-actinin, talin and paxillin), PC-aggregation and formation of large membrane pores (Tan et al, 2009). Since crosslinking other PCspecific antibodies bound to hESCs is not cytotoxic, the association of mAb 84 to a unique PC epitope (or potentially other additional unknown epitopes on hESCs) induces cytoskeletal reassembly in advance of PC aggregation and pore formation.…”
Section: Podocalyxin Marks Embryonal Carcinomas and Embryonic Stem Cellsmentioning
confidence: 99%
“…Studies with antibody fragments revealed that cytotoxicity requires divalency with sufficient flexibility linking the antigen binding domains (Lim et al, 2011). Since pre-treatment of HES-3 hESC and NCCIT cultures with mAb 84 in vitro prevents teratoma formation in a severe combined immunodeficient (SCID) mouse xenograft model mAb 84 has potential applications in clearing tumour-forming undifferentiated hESCs from cultures of differentiated hESCs intended for cell-based, regenerative therapies (Choo et al, 2008;Tan et al, 2009). With respect to the treatment of cancer, a cytotoxic antibody like mAb 84 may also prove to be an effective oncolytic adjuvant therapy in germ-line tumours like testicular cancer (especially embryonal carcinoma subtype).…”
Section: Podocalyxin Marks Embryonal Carcinomas and Embryonic Stem Cellsmentioning
confidence: 99%